Contextual Dictionary of Chinese Cultural Knowledge
eReference.
Keywords: This dictionary contains nearly 1500 entries and constitutes a core of essential knowledge on Chinese culture in a systematized and modernized form. It offers a professional yet highly readable introduction to Chinese culture for a global academic audience. Organized by subject and keyword, the book is divided into six sections: philosophy and ideology, social governance, literature and history, art and aesthetics, humanities and geography, and artefacts and technology. It contains both core knowledge and diversified information, while covering both historical and contemporary aspects. The target audience chiefly includes sinologists and translators of Chinese books. The dictionary provides the latest information on the full range of Chinese knowledge, an accurate interpretation of Chinese culture, a logically arranged and accessible reference framework and a panoramic experience across the breadth of the subject. It enables readers to grasp the patterns of Chinese culture and its knowledge systems, while also gaining a deeper understanding of contemporary Chinese life.